Homography estimation with deep convolutional neural networks by random color transformations - Molina-Cabello, Miguel Ángel; Elizondo Acuña, David Alberto; Luque-Baena, Rafael Marcos; López-Rubio, Ezequiel (My University, 2019)
Most classic approaches to homography estimation are based on the filtering of outliers by means of the RANSAC method. New proposals include deep convolutional neural networks. Here a new method for homography estimation is presented, which supplies a deep neural homography estimator with color perturbated versions of the original image pair. The obtained outputs are combined in order to obtain a more robust estimation of the underlying homography. Experimental results are shown, which demonstrate the adequate performance of our approach, both in quantitative and qualitative terms.
Keywords: Redes neuronales; convolutional neural networks; computer vision; color transformations